FACTOR ANALYSIS AND INDIVIDUAL PROGNOSIS FOR THE PATIENTS WITH FIRST REVEALED ARTERIAL HYPERTENSION - L. V. Salamatina; L. S. Zorina; S. A. Tokarev (Российский кардиологический журнал)
Aim. To study the risk factor (RF) prevalence, target organ damage (TOD) and overall cardiovascular risk among patients with the first time revealed AH. Material and methods. Totally 90 patients included (48 women, 42 men) with increased blood pressure (BP) from those who requested medical care for the first time. After investigation the evaluation of cardiovascular risk was done according to National guidelines for Prophylaxy, diagnostics and treatment of AH, scales SCORE and PROCAM.Results. Most patients had 2 or more RF. Absence of additional cardiovascular risk factors among patients with the first time revealed AH existed only for women; 29,2% women and 14,3% men had 1 RF The prevalence of 2 RF was the same for both genders: 42,9% and 43,8%, resp. Three and 4 RF were twice more prevalent in men, than in women.Conclusion. In the population of patients with the first time revealed AH the average and high risk of cardiovascular complications was more common.